VD_FINDINFO Décision / 2016 / 231 vom 6. April 2016 - VD Tribunal cantonal (2016)
ORDONNANCE DE CONDAMNATION, FICTION DE LA NOTIFICATION, OPPOSITION TARDIVE | 356 al. 2 CPP (CH), 88 al. 1 CPP (CH), 88 al. 4 CPP (CH)